Workplace size and sickness absence transitions - Karl-Oskar Lindgren (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2012)
This study examines how workplace size relates to transitions in- and out-of sickness absence. Overall, the study finds important differences in the long-term sickness absence behavior of individuals working in small and large workplaces. In particular, the results show that the sickness spells are of higher incidence, but somewhat shorter duration in large workplaces. However, the results also show that the strength of these relationships varies across different labor market groups. The analysis is based on rich administrative data from Sweden over the period 1994-2008.
Keywords: I13; J22; J23; 330; sickness absence; workplace size; hazard model; Erwerbsunfähigkeit; Arbeitsplatz; Moral Hazard; Schweden